PENGARUH LATIHAN MODIFIKASI PERMAINAN BULUTANGKIS TERHADAP PUKULAN LOB FOREHAND PADA SISWA EKSTRAKURIKULER SMA S PAMOR CIKAMPEK - Sany, Muhammad Hafizh; Nugroho, Setio; Kusuma Yuda, Aria (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of badminton game modification training on forehand lob shots. This study used a quantitative descriptive method with a pre-experimental experimental method of one group pretest-postest design. The population of this study were students who participated in extracurricular activities, with a research sample of 30 students. Data collection techniques using descriptive statistics. The data analysis process uses the IBM SPSS Statistics version 26 application, including descriptive statistical tests, normality tests, homogeneity tests, and hypothesis testing. The result is the average value of pretest 35.50 and posttest 42.83. Paired sample t-test significance = 0.0009 sig. (2-tailed) < 0.05, then H₀ is rejected and Hₐ is accepted, because the calculated t value is 50.272 > 2.000. The value of the results of descriptive statistical analysis with pretest scores obtained the average value (mean) = 35.50, (median) = 37.00, (mode) 35, (standard deviation) 6.022, (variance) 36.259, (minimum) 21, (maximum) 47. While the results of descriptive statistical analysis with posttest scores obtained the average value (mean) = 42. 83, (median) = 42.50, (mode) 41, (standard deviation) 3.395, (variance) 11.253, (minimum) 36, (maximum) 50. The conclusion of this study is that there is an effect of modification of badminton games on forehand lob shots on extracurricular students of SMA S Pamor Cikampek.